Breastfeeding Behavior and LATCH Score in Postpartum Mothers days 1-7 with Overweight and Obesity - Reni Yuli Astutik; Nining Istighosah; Retno Palupi Yonni Siwi (Journal Of Nursing Practice, 2024)
Background: Lifestyle changes during pregnancy tend to occur less frequently, and unhealthy eating patterns resulting from consuming fast food can trigger overweight and obesity. Existing research has revealed the influence of obesity on delayed lactogenesis II and low milk production but has not revealed the influence of obesity on breastfeeding behavior and the LATCH score as an early identification of breastfeeding success. Purpose: This study aim to analyzing the differences between overweight and obesity on breastfeeding behavior and LATCH scores in postpartum mothers on 1–7 days. Method: This research uses an analytical design with a observational approach. The sample for this study was all third-trimester primigravida mothers with normal pregnancies who checked themselves at the Kediri City Community Health Center and met the research inclusion criteria amount 86 samples. Breastfeeding behavior data and LATCH scores evaluate use quistionare were assessed on days 1, 3, and 7 days postpartum. Data analysis using SPSS version 26 with paired t test. Results: The breastfeeding behavior scores of both groups did not different at 1 day (45 ± 3.34 vs. 45 ± 3.34; P = 0.760), 3 days (78 ± 5.78 vs. 67 ± 9.03; P = 0.213), and 7 days (10 ± 0.59 vs. 8 ± 0.50; P = 0.087). There was no difference in LATCH scores at 1 day (3 ± 0.67 vs. 3 ± 0.45; P = 0.646) and 3 days postpartum (78 ± 5.78 vs. 6 ± 0.03; P = 0.098), but at 7 days postpartum between the two groups were significantly different (10 ± 0.59 vs. 8 ± 0.50; P < 0.001). Conclusion: The breastfeeding behavior and LATCH score can be used to predict difficulties in breastfeeding experienced by overweight and obese mothers postpartum for 1–7 days. Having an appropriate systematic assessment can help with timely intervention and improvements in breastfeeding techniques so increase breastfeeding success.